EKSISTENSI PENGELOLAAN ZAKAT MENURUT PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Saputra, Hendra Adi; Jamil, Sukran (Jurnal Muhakkamah, 2019)
Zakat is one of the Islamic Sharia which then made the Law on Zakat, namely Law Number 23 of 2011 concerning Management of Zakat, one of the benefits of zakat can be the welfare of the community, especially Muslims. The formulation of the problem in this study is how is the existence of zakat in the legislation in Indonesia. The research method used is the notative method with an analytical approach and legislation approach. The existence of zakat in legislation is evidenced by the existence of Law of the Republic of Indonesia Number 23 of 2011 concerning Management of Zakat, Government Regulation of the Republic of Indonesia Number 14 of 2014 concerning the Implementation of Law number 23 of 2011 concerning Management of Zakat and Many Regional Regulations which are also issued regarding with the regulation of zakat one of which is the Regional Regulation of the Province of West Nusa Tenggara Number 9 of 2015 concerning the Implementation and Management of Zakat, donations and alms. for the management of zakat itself carried out by BAZNAS, the National Amil Zakat Agency is a non-structural government institution that is independent and is responsible to the President through the Minister. The duties include planning, collecting, distributing, and utilizing zakat.